Seasonal variation in the lower thermotolerance of adult New Zealand flower thrips Thrips obscuratus (Crawford) - McLaren, G.F.; Colhoun, K.M.; Butler, R.C (New Zealand Plant Protection, 2010)
The ability of New Zealand flower thrips (NZFT) to tolerate cold temperatures was investigated Thrips were collected from a range of natural sources in Central Otago over 2 years Some adult NZFT (predominantly females) survived for up to 2 months on peach fruit at 01C; LT 50 354 days and LT 99 707 days Plant material containing NZFT was exposed for 24 h to 10 75 5 25 and 0C and NZFT mortality measured Irrespective of the time of year when NZFT were collected mortality was similar after 24 h at 25C to that at 0C (means 46 47) but increased with decreasing temperature (mean mortality 225 at 5C 663 at 75C and 820 at 10C) From 75C downwards responses to changes in temperature varied between seasons (P